Fragments from a history of Muslim education in the Kazakh steppe at the end of XIX – early XX centuries (Journal of history, 2020)
The article highlights the history of Muslim education in the Kazakh steppe at the end of XIX – early XX century, in the period of strengthening of the Russian colonial policy. The author examines the activities of traditional schools, showed growth of maktabe and madrasa, are disclosed processes of modernization in the Muslim education in the study period. Also, the article provides archival data for studying in madrassas «Muhammadiyah» and «Husain» from the Kazakh steppe. Published archival document on the biography of K. Zhubanov that he actually studied in madrassas «Husain». Key words: jadidism, enlightenment, secular education, maktaba, madrasa.